Synergetic Interfacial Tension Reduction Potential of Silica Nanoparticles and Enzyme - Udoh, Tinuola Hannah; Orodu, Oyinkepreye David (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
The co-existence of multiphase fluids in the hydrocarbon reservoir rock pores plays a fundamental role in oil recovery processes because of the strong effect of interfacial forces that exist at the interface of these immiscible fluids. In this study, the effects of enzyme and silica nanoparticles on crude oil-brine interfacial tension were investigated under varied brine salinities and brine compositions. The results showed that the application of silica nanoparticles alone in brines of varied compositions and salinities does not significantly modify the crude oil-brine IFT. The use of enzyme and combined enzyme-nanoparticles however significantly reduced crude oil-brines IFT but the contribution of silica nanoparticles to the IFT reduction was not significant. The result of this study is relevant to the design and applications of enzyme and nanoparticles enhanced oil recovery processes.